Multiply the numerator by the reciprocal of the denominator.

To write <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> as a fraction with a common denominator, multiply by <math><mstyle displaystyle="true"><mfrac><mrow><mi>x</mi><mo>-</mo><mn>1</mn></mrow><mrow><mi>x</mi><mo>-</mo><mn>1</mn></mrow></mfrac></mstyle></math> .

Combine <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mi>x</mi><mo>-</mo><mn>1</mn></mrow><mrow><mi>x</mi><mo>-</mo><mn>1</mn></mrow></mfrac></mstyle></math> .

Combine the numerators over the common denominator.

Rewrite <math><mstyle displaystyle="true"><mfrac><mrow><mi>x</mi><mo>-</mo><mrow><mo>(</mo><mi>x</mi><mo>-</mo><mn>1</mn><mo>)</mo></mrow></mrow><mrow><mi>x</mi><mo>-</mo><mn>1</mn></mrow></mfrac></mstyle></math> in a factored form.

Apply the distributive property.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> from <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Multiply the numerator by the reciprocal of the denominator.

Factor <math><mstyle displaystyle="true"><mi>x</mi><mo>-</mo><mn>1</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>1</mn><mrow><mo>(</mo><mi>x</mi><mo>-</mo><mn>1</mn><mo>)</mo></mrow></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Do you know how to Simplify (x/(x-1))/(x/(x-1)-1)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.